2001
DOI: 10.1093/jexbot/52.358.971
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tolerance of transgenic poplar plants overexpressing γ‐glutamylcysteine synthetase towards chloroacetanilide herbicides

Abstract: A wild-type poplar hybrid and two transgenic clones overexpressing a bacterial gamma-glutamylcysteine synthetase in the cytosol or in the chloroplasts were exposed to the chloroacetanilide herbicides acetochlor and metolachlor dispersed in the soil. The transformed poplars contained higher gamma-glutamylcysteine and glutathione (GSH) levels than wild-type plants and therefore it was supposed that they would have an elevated tolerance towards these herbicides, which are detoxified in GSH-dependent reactions. Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(65 citation statements)
references
References 34 publications
4
60
0
1
Order By: Relevance
“…Overexpression of enzyme glutathione synthetase involved in GSH biosynthesis showed no effect on GSH level and was not sufficient to improve ozone tolerance [137] and resistance to photoinhibition [138] in hybrid poplar (Populus tremula × P. alba). However, overexpression of γ-ECS showed reduced sensitivity towards cadmium stress in Indian mustard [139] and enhanced tolerance towards chloroacetanilide herbicides in poplar plants [140]. Eltayeb and coworkers [141] observed greater protection against oxidative damages imposed by various environmental stresses in transgenic potato with higher level of reduced glutathione.…”
Section: Glutathionementioning
confidence: 98%
“…Overexpression of enzyme glutathione synthetase involved in GSH biosynthesis showed no effect on GSH level and was not sufficient to improve ozone tolerance [137] and resistance to photoinhibition [138] in hybrid poplar (Populus tremula × P. alba). However, overexpression of γ-ECS showed reduced sensitivity towards cadmium stress in Indian mustard [139] and enhanced tolerance towards chloroacetanilide herbicides in poplar plants [140]. Eltayeb and coworkers [141] observed greater protection against oxidative damages imposed by various environmental stresses in transgenic potato with higher level of reduced glutathione.…”
Section: Glutathionementioning
confidence: 98%
“…Many of the poplar hybrid varieties have been genetically modified with microbial catabolic genes and specific transporters for increased remediation [141,142]. For example, mercuric reductase and γ-glutamylsysteine synthetase genes showed increased resistance to Hg and Cd and Cu, respectively, through accumulation of higher concentrations of these metals [119,142].…”
Section: Designer Plant Approachmentioning
confidence: 99%
“…Many of the poplar hybrid varieties have been genetically modified with microbial catabolic genes and specific transporters for increased remediation [141,142]. For example, mercuric reductase and γ-glutamylsysteine synthetase genes showed increased resistance to Hg and Cd and Cu, respectively, through accumulation of higher concentrations of these metals [119,142]. As mentioned earlier, manipulation of desired plant species with multiple genes will facilitate complete degradation of pollutants to ensure that the harvested biomass can be utilized completely for additional benefits [143].…”
Section: Designer Plant Approachmentioning
confidence: 99%
“…Previous studies have demonstrated that enhanced GSH level can significantly induce tolerance against various environmental stress conditions (Noctor et al, 1998;Zhu et al, 1999;Gullner et al, 2001; Gomez et al, Figure 1. Characterization of T4 generation AtECS lines.…”
mentioning
confidence: 95%